Batu Bernada di Ulahahan: Ide Pembuatan dan Organologi Alat Musik Batu “Pele Vatwam” - Nelsano A. Latupeirissa (Journal of Music Science, Technology, and Industry, 2022)
Purpose: This article is an organology study and a report on the exploration and development process of a traditional musical instrument called Pele Vatwam. Research Methods: this study uses a qualitative descriptive method. Results and Discussion: This musical instrument has its own uniqueness, the basic material for making this musical instrument is from natural flat andesite stones located on the coast of Telutih bay, the stones are collected and tuning the tone through a tuner application without the process of cutting or scraping the stone with using a cutter or machine to produce a pitched stone. Implication: Efforts to develop the traditional musical instrument Pele Vatwam can be one of the riches and uniqueness of musical culture on Seram Island, Maluku.